2002
DOI: 10.1006/jabr.2001.9049
|View full text |Cite
|
Sign up to set email alerts
|

Automorphisms of Coxeter Groups of Rank 3 with Infinite Bonds

Abstract: If W is a rank 3 Coxeter group, whose Coxeter diagram contains at least one infinite bond, then the automorphism group of W is larger than the group generated by the inner automorphisms and the automorphisms induced from automorphisms of the Coxeter diagram. In each case the automorphism group of W is described. PRELIMINARIESThe aim of this paper is to describe the automorphism group of rank 3 Coxeter groups whose diagram contains at least one infinite bond.We recall that a Coxeter group is a group with a pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 9 publications
(9 reference statements)
0
15
0
Order By: Relevance
“…In this situation we write w| J and w| K for the images of w ∈ W under the natural projections W → W J and W → W K , so that w = w| J · w| K = w| K · w| J . We will need the following fact: Proposition 3.1 (Franzsen and Howlett [8]). If v ∈ W then v −1 sv ∈ S for all s ∈ S if and only if v = w J for a subset J ⊂ S which commutes with S \ J and which is such that W J is finite.…”
Section: Duality For Twisted Involutionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this situation we write w| J and w| K for the images of w ∈ W under the natural projections W → W J and W → W K , so that w = w| J · w| K = w| K · w| J . We will need the following fact: Proposition 3.1 (Franzsen and Howlett [8]). If v ∈ W then v −1 sv ∈ S for all s ∈ S if and only if v = w J for a subset J ⊂ S which commutes with S \ J and which is such that W J is finite.…”
Section: Duality For Twisted Involutionsmentioning
confidence: 99%
“…This implies that (a) and (b) hold by Proposition 2. 8. Alternatively suppose us < u; one of the following cases then occurs:…”
Section: Lemma 411 (See [2]mentioning
confidence: 99%
“…The automorphism groups of infinite rank 3 Coxeter groups whose diagrams have no edges with infinite labels are described in [9]; in this case the automorphism group is the semi-direct product of Inn(W ) and the group of graph automorphisms. The automorphism groups of rank 3 Coxeter groups with both finite and infinite edge labels are described in [7].For the purposes of this paper, we say that an infinite Coxeter group is nearly finite if it has finite rank n and has a finite parabolic subgroup of rank n − 1. It is shown that if W is nearly finite and does not have an edge labelled ∞ then the group of all automorphisms of W that preserve reflections is the semi-direct product of Inn(W ) and the group of graph automorphisms.…”
mentioning
confidence: 99%
“…Finally, in [14], Mühlherr gave a presentation for the automorphism group of any right-angled Coxeter group. The automorphism groups of infinite rank 3 Coxeter groups whose diagrams have no edges with infinite labels are described in [9]; in this case the automorphism group is the semi-direct product of Inn(W ) and the group of graph automorphisms. The automorphism groups of rank 3 Coxeter groups with both finite and infinite edge labels are described in [7].…”
mentioning
confidence: 99%
See 1 more Smart Citation